2020
DOI: 10.1680/jgeot.18.p.302
|View full text |Cite
|
Sign up to set email alerts
|

Monopile rotation under complex cyclic lateral loading in sand

Abstract: Monopiles supporting offshore wind turbines experience combined moment and horizontal loading which is both cyclic and complex – continuously varying in amplitude, direction and frequency. The accumulation of rotation with cyclic loading (ratcheting) is a key concern for monopile designers and has been explored in previous experimental studies, where constant-amplitude cyclic tests have shown rotation to accumulate as a power-law with cycle number. This paper presents results from laboratory tests in dry sand,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 35 publications
1
16
0
3
Order By: Relevance
“…Energies 2020, 13, 3915 10 of 22 might be due to multiple reasons, including the size and scale of each test, number of loading cycles, the rate of loading, the amplitude (intensity) of loading, the installation method, and the total time of each test. Method compared to and validated against Li et al [10] Richards et al [17] Laboratory scaled tests for rigid monopiles in sand Partial two-way loading results in a much higher degradation and leads to more rotation accumulation than one-way loads, however with a smaller factor than LeBlanc et al [11] Tests were performed on a rigid pile in sands for up to 10,000 loading cycles. The response of the monopile to multi-directional storm loading was also studied…”
Section: The Differences In Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Energies 2020, 13, 3915 10 of 22 might be due to multiple reasons, including the size and scale of each test, number of loading cycles, the rate of loading, the amplitude (intensity) of loading, the installation method, and the total time of each test. Method compared to and validated against Li et al [10] Richards et al [17] Laboratory scaled tests for rigid monopiles in sand Partial two-way loading results in a much higher degradation and leads to more rotation accumulation than one-way loads, however with a smaller factor than LeBlanc et al [11] Tests were performed on a rigid pile in sands for up to 10,000 loading cycles. The response of the monopile to multi-directional storm loading was also studied…”
Section: The Differences In Resultsmentioning
confidence: 99%
“…Furthermore, the model testing setup is usually solely either one-way or two-way, whereas the loading on an offshore wind foundation is a combination of the two with cyclic load packets of different means and ranges. However, recent scaled tests by Richards et al [17], Truong et al [18], and Abiker and Achmus [19] show that the effect of two-way loading is less severe than the ones previously reported in LeBlanc et al [11]. It is shown that the load factor for partial two-way loading factor T c can be reduced from 4, as originally presented, to a number in the range of 2-3, which has a significant impact on the effect of accumulated rotation considering the total number of cycles in a given storm.…”
Section: Additional References In Sandmentioning
confidence: 99%
“…Monopiles with a diameter of 4-10 m and a length-to-diameter ratio of 3-6 are widely used as foundations for offshore wind turbines (OWTs), though to date limited guidance on evaluating the lateral response has been given in design guidelines such as DNVGL (2016). The conventional p-y method (API, 2011;Matlock, 1970;Reese et al, 1974) developed for long slender piles subjected to limited number of load cycles are not applicable for large-diameter monopiles used for OWTs (Abadie et al, 2019;Achmus et al, 2009Achmus et al, , 2005Bayton et al, 2018;Byrne et al, 2015;LeBlanc et al, 2010;Richards et al, 2019;Wu et al, 2019;Zdravković et al, 2015, among others). Significant improvements in the design methods have been achieved in the last few years through two well-known joint industry projects, PISA (Byrne et al, 2019) and REDWIN (Skau et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…So, they are recommended by DNV (DET NORSKE VERITAS) code to be the well suited foundation type in the offshore wind power industry for water depths below 25 m [1]. Richards and Byrne [2] pointed out that 87% of the built foundations of offshore wind turbines are monopile foundations with large diameters. In recent years, monopiles are also widely used in Jiangsu, Zhejiang and other coastal areas of China where the surface layer of the seabed is mostly soft soil, while the bottom layer of the seabed is mainly fine sand.…”
Section: Introductionmentioning
confidence: 99%
“…Model experiments: Goit et al [22] conducted dynamic experiments model soil-pile tests on a shaking table; Bhattacharya et al [23] studied dynamic soil-pile interaction using a 1 g scale model test; Manna and Baidya [24] calculated the dynamic stiffness and damping of a slender pile and observed that the stiffness and damping decrease as the amplitude of load increases; Mohamed and Hesham [25] investigated the lateral vibration performance of two full-scale large-capacity helical piles and one driven pile installed in overconsolidated and structured clay, and observed a similar phenomenon to Manna and Baidya [24]; Lombardi et al [5] investigated changes in pile natural frequency and damping after 32,000-172,000 cycles of horizontal loading; He et al [26] studied the decreases of the pile's natural frequencies with the existence of a scour hole; Futai et al [4] measured the natural frequency of piles in centrifuge tests by FFT (Fast Fourier Transform), and investigated the influences of the density of sand and the ratio of free length to embedded depth; Leblanc et al [27] carried out a series of laboratory tests where a stiff pile in dry sand was subjected to 8000-60,000 cycles of combined moment and horizontal loading, and presented the accumulated rotation and changes in stiffness after long-term cyclic loading; Richards et al [2] presented results from laboratory tests in dry sand, which explored pile rotation with multidirectional cyclic loadings.…”
Section: Introductionmentioning
confidence: 99%